Pertanggungjawaban Para Pihak Yang Terlibat Dalam Perjudian Poker Online - Trinita Calista Ruhulessin; Elsa Rina Maya Toule; Jacob Hattu (PATTIMURA Law Study Review, 2023)
ABSTRACT: Gambling is a crime, namely betting an amount of money where the winner gets the betting money or in other words a battle of fate. The problem of gambling can be detrimental to society and the morals of our nation, basically this crime causes public order, peace and security to be disrupted. Besides that, the influence on children is very large, they will join in committing gambling crimes that they see happening in their environment, which will negatively affect the psychology of children and cause material losses for those who do it. Even though the prohibition of gambling both offline and using electronic media or more familiarly known as online gambling has been very strictly regulated in several laws and regulations, in fact this gambling is increasingly widespread in society. Even with the many regulations that tighten the scope of gambling, gamblers are even more innovative in running this business. Gambling means that an act can be punished by the existence of regulations. If someone has committed a crime of gambling, then he can only be tried based on the criminal laws and regulations that were in effect at the time the act was committed. Online gambling is one type of Cyber ​​Crime action. namely the misuse of technology for gambling, online gambling itself has been regulated in Law No. 11 of 2008 concerning Information and Electronic Transactions. And the article that regulates online gambling is listed in article 27 paragraph 2.